Search for Lorentz-invariance violation with the first KATRIN data - Aker, Max; Rodejohann, Werner; Spanier, Felix (Physical review, 2023)
Some extensions of the Standard Model of particle physics allow for Lorentz invariance and charge-parity-time invariance violations. In the neutrino sector strong constraints have been set by neutrino-oscillation and time-of-flight experiments. However, some Lorentz-invariance-violating parameters are not accessible via these probes. In this work, we focus on the parameters (a(3)of)00, (a(3)of)10, and (a(3)of)11 which would manifest themselves in a nonisotropic β-decaying source as a sidereal oscillation and an overall shift of the spectral endpoint. Based on the data of the first scientific run of the KATRIN experiment, we set the first 90% confidence-level limit on |(a(3)of)11| of <0.9×10−6 GeV to 3.7×10−6 GeV, depending on the phase. Moreover, we derive new constraints on (a(3)of)00 and (a(3)of)10.
Gesehen am 26.06.2023